Major Bovine Parasitic Zoonosis at Selected Municipal Abattoirs, North Shewa Zone, Oromia, Central Ethiopia - Said Muhammedand Tadesse Birhanu (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Bovine parasitic zoonoses have emerged from time to time and public health threat in developing countrieswhere eating of raw meat and improper disposal of condemned are practiced. However, there is a limited prevention and control strategy of the diseases including North Shewa Zone, Oromia, Ethiopia because of negligence. Moreover, there is a paucity of information regarding Bovine parasitic zoonosis in the areas. Hence, the current study was designed from October, 2019 to July, 2020 to determine major Bovine parasitic zoonoses at selected Municipals Abattoirs (Fitche, Kuyu and Shararo) of North Shewa zone, Oromia, Ethiopia.Purposive sampling technique was used to study Abattoirs whereas; simple random sampling was used to select study participants. Anti-mortem and post-mortem inspection were applied by using standard producers. Primary and qualitative data were used in this study. Out of 384 inspected cattle, 218 (56.8%) animals were condemned its organs during postmortem inspection. Among those 195(50.8%), 402 (52.3%), 11 (2.9%) and 16 (2.1%) animals' liver, lungs, heart and kidneys were condemned, respectively. The prevalence of Fasciolosis, Hydatidiosis and bovis Cysticercosis were found to be 52.3%, 27.2% and 2.90%, respectively. Among associated risk factors, poor body conditioned animals were the most susceptible (95.4%) as compared to medium (86.9%) and good (35.3%) in which body condition animals with statistically significant (p<0.05). The prevalence of bovine parasitic zoonoses among age groups young animals were the most susceptible compared with adults and also associated significantly (p<0.05). In contrast, the presence of the diseases was found to be insignificantly associated with the breeds (p>0.05). The study concluded that bovine parasitic zoonoses were the major public health problems in the study areas. Thus, community health education is urgently needed creation responsible bodies including Salale University. Moreover, further studies will be conducted in other municipal abattoirs in this zone.